Draft of the MEPS and HEPS for hair dryer in Thailand - Somchai Pattana (2018)
© 2017 The Authors. Published by Elsevier Ltd. Each year, about a million new hair dryers has been sold in the Thailand's market. Only safety standard is applied without the high efficiency performance standard (HEPS). This study is to setup the HEPS and minimum energy performance standard (MEPS) including the test method. First, market survey is done. By applying the Yamane statistic model, the number of sample are chosen and tested by the IEC 61855:2003 Household electrical hair care appliances - Methods of measuring the performance. It is found that for the hair dryer rated power equal or less than 1,300 Watt, 1,301- 1,900 Watt and 1,901 - 2,800 Watt, the MEPS are 5.9, 7.0 and 7.5 respectively. For the HEPS, they are 4.5, 5.4 and 5.7 respectively. If these figures is enforced, yearly potential saving will be 9,111,131 kWh.